2018
DOI: 10.1029/2018gl080470
|View full text |Cite
|
Sign up to set email alerts
|

Fault Reactivation by Fluid Injection: Controls From Stress State and Injection Rate

Abstract: We studied the influence of stress state and fluid injection rate on the reactivation of faults. We conducted experiments on a saw cut Westerly granite sample under triaxial stress conditions. Fault reactivation was triggered by injecting fluids through a borehole directly connected to the fault. Our results show that the peak fluid pressure at the borehole leading to reactivation increases with injection rate. Elastic wave velocity measurements along‐fault strike highlight that high injection rates induce sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 53 publications
5
89
0
Order By: Relevance
“…We conclude that simple effective stress laws that consider a uniform pore pressure distribution in a fault of simple geometry is often not adequate for the prediction of fault reactivation in shale formations. This finding is consistent with Passelègue et al (2018) who showed at laboratory scale that a nonlocal rupture initiation criterion should be considered to describe fault reactivation because of the fluid pressure heterogeneity within the fault.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We conclude that simple effective stress laws that consider a uniform pore pressure distribution in a fault of simple geometry is often not adequate for the prediction of fault reactivation in shale formations. This finding is consistent with Passelègue et al (2018) who showed at laboratory scale that a nonlocal rupture initiation criterion should be considered to describe fault reactivation because of the fluid pressure heterogeneity within the fault.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, during laboratory tests on fractures without filling, Barton et al (1985) and Olsson and Barton (2001) demonstrated that the coupling between fracture shear displacement or normal closure and fracture hydraulic conductivity variations depended both on the stress conditions and on fracture surface characteristics such as the roughness. Recent laboratory results highlight that the variation in effective normal stress related to local fluid injection in a fault plane does not imply complete separation of the two sides of a fault because complex channeling effects may favor heterogeneous pore pressure variations within the fault plane controlling leakage and nonlocal rupture initiation before the Coulomb rupture criterion is exceeded (Passelègue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fluid injection into a saw-cut granite sample in stress relaxation test shows that the onset of fault activation may not be predicted by equation 1 at high injection rates. This is presumably caused by a significantly heterogeneous distribution of fluid pressure on the fault plane (Noël et al, 2019;Passelègue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, stress drop occurs due to the compression acted on the sample by actuator piston drops in response to fracture slip, and the fracture slips slows down and finally ends at a lower stress level. Later, Passelègue et al () also used a similar constant piston‐displacement control to study the distribution of pressure and effective stress in a fracture.…”
Section: Experimental Methodsmentioning
confidence: 99%